Analisis Faktor Risiko Terhadap Mortalitas Pasien Sepsis di Ruang Intensive Care Unit (ICU) RSUD DR. H. Abdul Moeloek Provinsi Lampung Tahun 2018-2021 - Putri Grace Aiko Purba; Ari Wahyuni; Novita Carolia; Liana Sidharti (Medula, 2026)
Sepsis is an organ dysfunction due to dysregulation of infection response. It is characterized by cardinal inflammatory signs such as vasodilation, leukocyte accumulation, and increased microvascular permeability in tissues away from the site of infection. Sepsis is identified using clinical criteria, specifically the Sequential (Sepsis-Related) Organ Failure Assessment Score with ≥2 points. Sepsis is a leading cause of mortality in the Intensive Care Unit. Its mortality is triggered by several risk factors, including age, low Glasgow Coma Scale and Mean Arterial Pressure scores, and the presence of comorbidities. This study aims to analyze the relationship between these determinants and mortality among the Intensive Care Unit sepsis patients. This study used an observational analytic method with a cross-sectional approach. The subjects were sepsis patients in the Intensive Care Unit of RSUD DR. H. Abdul Moeloek Lampung in 2018-2021 who met the inclusion and exclusion criteria. The independent variables were age, Glasgow Coma Scale, Mean Arterial Pressure, and comorbidities, while the dependent variable was mortality. Samples were collected using total sampling technique. The results showed that age, Glasgow Coma Scale, Mean Arterial Pressure, and comorbid disease were significantly associated sepsis mortality, with p-values of 0.008, 0.029, 0.040, and 0.013, respectively. Thus, there is a relationship between age, Glasgow Coma Scale, Mean Arterial Pressure, and comorbid disease to the mortality among sepsis patients.